The power of stories: A framework to orchestrate reflection in urban storytelling to form stronger communities. (2nd January 2023) - Slingerland, Geertje; Kooijman, Julia; Lukosch, Stephan; Comes, Tina; Brazier, Frances
ABSTRACT: This paper focuses on the particular power of storytelling to foster reflection and connections between people in urban life. In fact, the core principles and mechanisms for public storytelling to achieve this have yet to be made explicit. This gap is addressed by introducing a novel reflective storytelling framework that unveils the underlying principles of fostering reflection and connection through public storytelling. The framework is proposed on the basis of the literature and its appropriateness is explored in a case study in the Hague (the Netherlands) with particular focus on the influence of content and form on successfully orchestrating reflective storytelling. The impact of citizen stories on the creation of new and stronger social ties, as well as challenges, tensions, and opportunities are discussed. These results inform researchers, urban planners, and other city practitioners on how to design effective storytelling initiatives to strengthen ties in urban communities.